Entrepreneurship and Firm Performance in Sub-Saharan Africa - Ramachandran, Vijaya; Shah, Manju Kedia (World Bank, Washington, DC, 2012)
The development of the private sector in Sub-Saharan Africa is of crucial importance to the overall rate of economic growth of the region. Entrepreneurial firms have a prominent role in the private sector in many countries in the region. This analysis measures the impact of various entrepreneurial characteristics on the rate of firm growth. The analysis uses data from the Regional Program on Enterprise Development (RPED) at the World Bank. Approximately 200 firms in Kenya, Zimbabwe, Zambia, and Tanzania were surveyed in each country in the food processing, textile, furniture, and metalworking sectors; only the subset of firms owned by entrepreneurs is used in this study.